1970
DOI: 10.1056/nejm197002192820802
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent Examination of Biopsies from Long-Term Renal Allografts

Abstract: Immunofluorescent examination of open renal biopsies revealed clear-cut glomerular localization of immunoglobulins not related clearly to the quality of donor-recipient histocompatibility in 19 of 34 renal allografts. The biopsies were obtained 18 to 31 months after transplantations primarily from related donors with a variable quality of histocompatibility match. IgG was the predominant immunoglobulin class fixed in 13 biopsies, and IgM in six. The pattern of immunoglobulin deposition was linear, connoting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Morphological and immunopathological studies of human renal [1][2][3][4][5][6][7][8][9] and cardiac 10,11 allografts have shown that circulating immunoglobulins and complement probably play an important part in the rejection of these organs. In this report we seek evidence of the same mechanism in hepatic allografts.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and immunopathological studies of human renal [1][2][3][4][5][6][7][8][9] and cardiac 10,11 allografts have shown that circulating immunoglobulins and complement probably play an important part in the rejection of these organs. In this report we seek evidence of the same mechanism in hepatic allografts.…”
Section: Introductionmentioning
confidence: 99%
“…Observed patterns of Ig in allografts were linear in seven kidneys, granular in three and indeterminate in four. Three of these patients had received ATG (patients J. W., M. B., and M. C.); direct IF was negative for horse globulin fixation, as it was also in patient T. T. Survey of one series of long-functioning, living related-donor allografts by immunohistochemical analyses of surgical biopsies indicated a high frequency of immunoglobulin-associated glomerular abnormalities (23). Moreover, the report documented in that group the apparent incidence of linear and other patterns of host immunoglobulin localization, presumptive of anti-GBM, and soluble antigen antibody complex-mediated glomerulonephritis.…”
Section: Methodsmentioning
confidence: 93%
“…A number of other tests for rejection have been devised which generally depend on looking at the products of secondary damage to the graft, including lysozymuria (8), elevation of blood and urinary histamine (18), and increased urinary FDP (1)(2)(3)5,9,21,25). Renal biopsies have been studied for this purpose (17), but there is no morphological finding that is completely specific for rejection.…”
Section: Discussionmentioning
confidence: 99%